2012
DOI: 10.5152/akd.2013.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nebivolol on endothelial dysfunction in patients with Behçet’s disease; a prospective single-arm controlled study

Abstract: Objective: Behçet's disease (BD) is a systemic vasculitis, capable of involving all types of vessels. Endothelial dysfunction (ED) has been previously documented in BD. Previous studies showed that nebivolol might improve endothelial functions in endothelial dysfunction. The aim of our study is to assess the effects of nebivolol on endothelial dysfunction in patients with Behçet's disease. Methods: This study was designed as prospective single-arm controlled study. We prospectively studied 35 Behçet's patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…CRP decreases NO release by showing effects on the enzyme nitric oxide synthase. Increased hs-CRP levels have been shown in BD and CRP levels may decrease with nebivolol therapy (14). Studies have demonstrated that CRP is interrelated and associated with interatrial electromechanical delay and AF (48,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP decreases NO release by showing effects on the enzyme nitric oxide synthase. Increased hs-CRP levels have been shown in BD and CRP levels may decrease with nebivolol therapy (14). Studies have demonstrated that CRP is interrelated and associated with interatrial electromechanical delay and AF (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were ultrasonographically documented endothelial dysfunction evaluated with flow-mediated dilatation method and a stable condition (14,15). Exclusion criteria were as follows: (1) impaired cardiopulmonary function, defined as the occurrence of respiratory failure, pulmonary infection or congestive heart failure; (2) coronary artery disease, defined as having a typical angina pectoris, history of a prior myocardial infarction, presence of a positive stress test or positive coronary angiographic findings; (3) valvular disease, atrial fibrillation, atrioventricular block or congenital heart disease; (4) hypertension, diabetes, dyslipidemia low-density lipoprotein (LDL) cholesterol >160 mg/dL, total cholesterol >240 mg/dL, triglyceride >200 mg/dL), using antihypertensives, antidiabetics and lipid-lowering treatment; (5) chronic alcoholism and smoking; (6) malignancy, hyperthyroidism and hypothyroidism; (7) use of any vasoactive drug; (8) renal and liver insufficiency; (9) vitamin B12 or folic acid deficiency; (10) active phase of BD clinically.…”
Section: Methodsmentioning
confidence: 99%